Resistance factors in the implementation of software process improvement project - Nasir, M.H.N.M.; Ahmad, R.; Hassan, N.H. (2008)
Over decades, software model for improving the quality of software through management of the software process has became significant in the software industry. Many companies are now being assessed according to standards such as the CMM, SIX-SIGMA or ISO 9000, which have brought substantial profit to the companies that utilize them to improve the quality of software product. Several companies in Malaysia have been carried out software process improvement projects. However, a software process improvement initiative is still sometimes delayed, costs are over budgeted and some of them surrender before the project ends. Therefore, this paper attempt to analyze and identify the resistance factors which influence the implementation of the software process improvement project initiated by the company. This paper will serve as reference to the professionals in the area. In the other hand, it may also helping the other companies to manage future projects through the use of preventive actions that will eliminate or at least lessening the resistance factors' consequences during the implementation of the software process improvement projects. This paper present a survey with 8 Malaysia's companies around Kuala Lumpur and Selangor which have an experience in initiating and conducting software process improvement project. A total of 117 respondents from various background have participated this survey.